2016
DOI: 10.1007/978-3-319-40548-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Pet Empires: Combining Design Thinking, Lean Startup and Agile to Learn from Failure and Develop a Successful Game in an Undergraduate Environment

Abstract: Startups are able to produce software products with a strong impact on the market, significantly contribution to the global economy. However, eight of ten software startups fail within their first three years -the main failure is caused by the high cost of getting the first customer and the even higher cost of getting the product wrong. In order to reduce these failures, more recent research has focused on combining the approaches of Design Thinking (DT), Lean Startup and Agile to develop and scale new product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…This means that the eLibrary performance relies on their BT advantages. Our results indicated that PEU influences PU to support H7, and this is in line with the other studies (de Paula and Araújo, 2016). According to our results, if a new technology adoption is free of effort, adopting any new technology (BT) is useful because they will obtain maximal benefit from BT accessing the digital library database.…”
Section: Discussionsupporting
confidence: 93%
“…This means that the eLibrary performance relies on their BT advantages. Our results indicated that PEU influences PU to support H7, and this is in line with the other studies (de Paula and Araújo, 2016). According to our results, if a new technology adoption is free of effort, adopting any new technology (BT) is useful because they will obtain maximal benefit from BT accessing the digital library database.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to Europe, a number of papers report research conducted in other locations, with a small representation of Brazil (Melegati et al , 2019; de Paula and Araujo, 2016; Tolfo et al , 2018; Ximenes et al , 2015), the USA (Kumar et al , 2018; May, 2012), China (Li et al , 2014; Yang et al , 2019), Indonesia (Nirwan and Dhewanto, 2015), Singapore (Chan et al , 2019) and Malaysia (Ekpe et al , 2017). The small number of investigations outside Europe highlights the lack of research and opportunities in other continents, especially in developing countries.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Similarly, there seems to be special attention given to combining LS with design thinking in software project management and process improvements (Ahmed et al , 2019; Edison et al , 2018; de Paula and Araujo, 2016; Risku and Abrahamsson, 2015; Ximenes et al , 2015) for further problem exploration. Design thinking is a methodology proposed by Brown (2009) that – differently from LS, which starts with a business idea – is triggered from a problem or question and is highly recognized in literature by its appeal to creativity, problem solving and user centeredness (Micheli et al , 2019).…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tasks were planned and delivered within twoweek periods and weekly meetings allowed an iterative review of the progress, questions to be raised, and reflections to be shared. Agile iterative practices are commonly used in software development practices and closely tie in with design thinking practices [72][73][74][75].…”
Section: Process Activities: How We Engagementioning
confidence: 99%